Cyanobacterial NDH-1 Complexes - Hualing, Mi (Frontiers in Microbiology, 2022)
Light reaction of photosynthesis is efficiently driven by protein complexes arranged in an orderly in the thylakoid membrane. As the 5th complex, NAD(P)H dehydrogenase complex (NDH-1) is involved in cyclic electron flow around photosystem I to protect plants against environmental stresses for efficient photosynthesis. In addition, two kinds of NDH-1 complexes participate in CO2 uptake for CO2 concentration in cyanobacteria. In recent years, great progress has been made in the understanding of the assembly and the structure of NDH-1. However, the regulatory mechanism of NDH-1 in photosynthesis remains largely unknown. Therefore, understanding the regulatory mechanism of NDH-1 is of great significance to reveal the mechanism of efficient photosynthesis. In this mini-review, the author introduces current progress in the research of cyanobacterial NDH-1. Finally, the author summarizes the possible regulatory mechanism of cyanobacterial NDH-1 in photosynthesis and discusses the research prospect.